Pemikiran Pendidikan al-Ghazali - Sodiq, Muhammad Jafar (Literasi: Jurnal Ilmu Pendidikan, 2016)
There are many controversial views in assessing Al-Ghazali thought. For example, there is an opinion that the reason of Islam deterioration is caused by his categorisation of fard 'ain for Religious Studies, and fard kifayah for others. Abdulloh Mas'ud said that the dichotomy in education today can be traced to his categorisation. On the other hand, there are many defenders declared that al Ghazali is not responsible for this dichotomy, but he is the true defender of Islam. Even al-Zubaidi, he said that If there is a prophet after Muhammad, he would be al - Ghazali. Based on these controversies, this article will describe al-Ghazali's ideas about education in his two books, Ihya Ulumuddin and Ayyuhal Walad. This article concluded that al-Ghazali's ideas can not be separated from its socio-cultural context. With this perspective we can get a whole picture of al-Ghazali. He lived in a period of the emersion of various sects and schools (mazhab) in Islam, the deterioration of the Abbasid dynasty, and the golden age of the dynasty Saljuk until its collapse. Al-Ghazali's educational thought is an integral part of this dynamics Islamic civilization in general. Thus, Islamic education also should not be alienated from the economic, political and social conditions that affect and determine the direction and the shape of Islamic civilization.